Stevens-Johnson Syndrome - clinical symptoms, etiology, pathophysiology and medical treatment - a review of the literature - Karolina Szymkiewicz; Aleksandra Marczak; Michalina Hordejuk; Michał Hyjek (Kazimierz Wielki University, 2022)
Stevens-Johnson syndrome (SJS) is a rare disease of the skin and mucous membrane. It develops as a result of a sudden skin reaction, which is most often triggered by the use of certain drugs. It is characterized by acute epidermal necrosis. The syndrome can lead to many complications and death. Currently, there are no guidelines and management schematics for this disease. Treatment has changed over the years due to the discovery of the possible pathomechanism of SJS. Nevertheless, because of the rarity of the disease, there is a lack of adequate prospective randomized studies that could provide valuable information on treatment.    Objective: The purpose of this study was to present Stevens-Johnson syndrome, including clinical features, etiology, pathomechanism, complications and treatment.   Methods: A literature search was performed in the PubMed medical publication database using the following keywords: Stevens-Johnson syndrome, acute drug-induced skin reaction, cutaneous adverse drug reactions.   Results: Stevens-Johnson syndrome is an example of an acute cutaneous reaction to certain medicinal substances. The pathomechanism is not fully understood. There is an association of genetics with the risk of developing symptoms of the syndrome in selected populations. Treatment formerly was based on glucocorticosteroids, but now IVIG (intravenous immune globulin) is used. Dehydration, pneumonia or sepsis may develop as a complication of the syndrome.     Conclusions: The discovery of a genetic predisposition to develop Stevens-Johnson syndrome offers the possibility of future effective disease prevention. It is necessary to create medical procedure schemes for the diagnosis and treatment of this disorder. The discovery of the possible pathomechanism has allowed the use of IVIG in the treatment of the syndrome. Effective and prompt diagnosis and treatment can prevent life-threatening complications and death from SJS.